(3GdYjhf GdZGeRI Ydi NHGjG GdQGeRIs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3YHO Gddg Hf eMeO GdNRQLj, VjGA GdOjf CHh eMeO,J (B626 (3g` s ((3ceGd GdOjf Hf eMeO GdeTghQ fSHg HGHf GdfGSN s)
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Edi Gdehdi GdZfi eMeO GHf CHj HcQ GdeNRhei GdMeO ddg GdPi TQM UOhQfG dSdhc YQhV GdESdGe CeG HYO adG jNai Cf GdYQhV UfGYI Jbje dHVGYI GdTYQ ai Shb GdeMGSf hRfkG s
(3BNQgG (B:s
(3Je GdcJGH hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hSde hfbd ef fSNI eUMMI bQFJ Ydi GdeUfa s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais